2011
DOI: 10.4209/aaqr.2011.05.0060
|View full text |Cite
|
Sign up to set email alerts
|

Filtration of Submicron Aerosol Particles Using a Carbon Fiber Ionizer-assisted Electret Filter

Abstract: The effects of a carbon fiber ionizer on the collection efficiency of an electret filter for residential house ventilation were investigated with varying the face velocity, the number of ionizers, and the polarity of the ionizer. A Flimmer filter, which was made by a Swedish company, was used as the electret filter. The air ion concentration upstream of the filter gradually increased as the velocity increased. Under the same conditions of velocity and the same number of ionizers, the positive ion concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 21 publications
0
19
0
1
Order By: Relevance
“…() was only 20% for 100‐ to 300‐nm particles at the relatively low air velocity of 0.4 m/s, whereas the air cleaner developed by Noh et al. () had an efficiency of 80% at 0.8 m/s. In the latter case, particle removal was enhanced by an electret filter, but the collection efficiency of the electret filter was only 60%, even when using four carbon fiber ionizers.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…() was only 20% for 100‐ to 300‐nm particles at the relatively low air velocity of 0.4 m/s, whereas the air cleaner developed by Noh et al. () had an efficiency of 80% at 0.8 m/s. In the latter case, particle removal was enhanced by an electret filter, but the collection efficiency of the electret filter was only 60%, even when using four carbon fiber ionizers.…”
Section: Introductionmentioning
confidence: 95%
“…() and Noh et al. () also developed air cleaners using fibrous and electret filters, which were electrostatically assisted by carbon fiber ionizers. The particle removal efficiency of the air cleaner developed by Park et al.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies that used an ionizer showed that the particle removal efficiency was improved from ~60% to 85% (Park et al, 2010;Noh et al, 2011). The efficiency could not be increased further, however, because of the upper limit of the unipolar ion concentration caused by mutual repulsion loss.…”
Section: Introductionmentioning
confidence: 96%
“…Introducing an ionizer in an electret filter system overcomes this drawback of the electret filter by supplying additional charges (Noh et al, 2011). Previous studies that used an ionizer showed that the particle removal efficiency was improved from ~60% to 85% (Park et al, 2010;Noh et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation